Hiperurisemia Pada Remaja di Wilayah Kerja Puskesmas Arjasa Kabupaten Situbondo Hyperuricemia in Adolescents (16-24 Years Old) in Arjasa Primary Health Center, Situbondo Regency - Riskotin Thayibah; Yunus Ariyanto; Andrei Ramani (Pustaka Kesehatan, 2018)
Abstract Hyperuricemia is a condition which there is an elevated of uric acid serum level above normal, whereas gout is a group of diseases caused by deposition of monosodium urate crystals in the tissues, due to metabolism disorders in the form of hyperuricemia. Most commonly experienced by the elderly, but this disease also can be experienced by elderly and young adolescents. The purpose of this study is to describe of hyperuricemia patients in adolescents (16-24 years) in Arjasa Primary Health Center (PHC) area of ​​Situbondo Regency, as many 11 people. The cross-sectional method is used in this study. We measure body mass index (BMI) and consumption pattern using food frequency questions (FFQ) method. Most of hyperurisemia patient in young adolescent are male, have good enough education level ie Senior High School, unemployement, have enough knowledge, have family income > 1,374,000, -, have a history of hyperuricemia in their family, obesity, consumption of high purine food ie offal, food and drink containing alcohol ie tapé, and do not consume of deuretic medicines. Keywords: Hyperuricemia, Adolescents